(untitled) - Brusic, Sharon (New York, N.Y., 2004)
This book is a technology literacy textbook for high school. It uses the systems approach (input, process, output, feedback) to inform students about communication and bio-related technology. The text teaches students about the nature of technology and its role in our lives. It provides information about the history and evolution of technology; the characteristics of technology; and its impact on our society, culture, economy, politics and environment
Keywords: Technology,Kỹ thuật; Study and teaching (Secondary),Dạy và học (trung học)